Family hardiness among primary caregivers of breast cancer patients in Hunan Province: a cross-sectional study exploring the relationship with attachment and caregiver preparedness - Sun, Xin; Xu, Lili; Sheng, Lijuan (Frontiers in Public Health, 2024)
BackgroundFamily hardiness is a key variable contributing to positive family functioning, which has significant effects on the quality of life and the mental health of patientsand caregivers. The factors that contribute to family hardiness support both the psychological and physical well-being of caregivers is unknown. More specifically, the relationship of family hardiness with attachment and caregiver preparedness has not been explored.AimThe current study aimed to investigate the family hardiness in caregivers of breast cancer patients and explore the relationship with attachment and caregiver preparedness and identify the associated factors.MethodsThis cross-sectional correlational study was conducted from March to July, 2022. 140 caregivers of breast cancer patients were recruited in two IIIA-grade hospitals in Hunan Province using convenience sampling. Data were collected using a personal characteristics questionnaire, The Family Hardiness Index (FHI), Caregiver Preparedness Scale (CPS), and the Experiences in Close Relationships Inventory-Revised Edition (ECR-R). Chi-square, Pearson’s correlation coefficient, generalized additive model and multiple logistic regression analyses were performed.ResultsA total of 140 caregivers participated in the study. The mean age of participants was (42.29 ± 14.54) years and most of them were male (57.1%). The mean FHI score of caregivers was 58.11 ± 5.67. Multiple linear regression analysis indicated that family hardiness is affected by ECR-R, CPS, education level, and knowledge of breast cancer. The score of CPS was positively associated with family hardiness (β = 0.265, p < 0.001), whereas ECR-R negatively predicted family hardiness (β = −0.078, p < 0.001).ConclusionFamily hardiness plays a critical role in helping caregivers manage the stresses associated with providing care to breast cancer patients. Enhancing caregiver preparedness and education, as well as addressing attachment-related issues, can significantly improve family hardiness. In light of our findings, we suggest that closer relationships within families, adding preparedness and knowledge of disease should be encouraged during the care of breast cancer patients.